In a rugged land : Ansel Adams, Dorothea Lange, and the Three Mormon towns collaboration, 1953-1954 - Swensen, James R. (The University of Utah Press, 2018)
"Though photographers Dorothea Lange and Ansel Adams were contemporaries and longtime friends, most of their work portrays contrasting subject matter. Lange's artistic photodocumentation set a new aesthetic standard for social commentary; Adams lit up nature's wonders with an unfailing eye and preeminent technical skill. That they joined together to photograph Mormons in Utah in the early 1950s for Life magazine may come as a surprise. In a Rugged Land examines the history and content of the two photographers' forgotten collaboration, Three Mormon Towns. Looking at Adams' and Lange's photographs, extant letters, and personal memories, the book provides a window into an important moment in their careers and seeks to understand why a project that once held such promise ended in disillusionment and is now little more than a footnote in their illustrative biographies. Swensen's in-depth research and interpretation helps make sense of what they did and places their efforts alongside others who were also exploring the particular qualities of the Mormon village at that time"--Provided by publisher.